Cross-national differences in determinants of multiple deprivation in Europe - Francesco Figari (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper analyses the relationship between deprivation, income and other individual dimensions over time, in eleven European countries, exploiting the longitudinal nature of the European Community Household Panel (ECHP). First, the determinants of deprivation are analysed by using fixed effects models for each country separately. Second a decomposition of the deprivation gaps between countries highlights the reasons for the differentials across Europe. The results show that changes in income and deprivation do not strictly coincide. In countries where deprivation is higher, income is more effective in reducing the deprivation differential but the family structure contributes to determine such a gap.
Keywords: 330